Eu não queria precisar lutar: a escrita de um romance - Siqueira, Yan Patrick Brandemburg (2021)
The area of study called Creative Writing comprises the production of literary works as an object of investigation. Within this area, this work is divided into two parts. The first part is a fictional narrative entitled Eu não queria precisar lutar, a dystopian novel centered on the trajectory of a Pataxó family facing the challenges of the dictatorship called Nova Democracy. The second part is an essay about the fictional creative process. In this section, not only the research done on dystopias, utopias and about the Pataxo people are discussed, but also the choices of literary techniques in the composition of the narrative are pondered.